Lightweight and Reliability Analysis of the Heavy Duty Driven Axle Housing based on the Finite Element Theory - Tuo Qianjin (Jixie chuandong)
Aiming at the problems of the process of driving heavy duty truck fuel consumption,higher manufacturing costs and so on,according to the finite element theory,the heavy duty truck driven axle housing lightweight design is carried out,and the light weight calculation results are imported into the finite element model to study the deformation of the axle housing before and after optimization at maximum load optimization uneven roads conditions of stress,life and safety coefficient changes.The results show that after the axle housing thickness lightweight size optimization,wheel area,leaf springs to the axle core area and axle core,the trend of the overall thickness of the axle housing is downward,there is no change to the wheel area to leaf spring transition area thickness.After the axle housing thickness lightweight size optimization,the trend of the total volume is a downward,the volume of the initial value is from 0.043m3 dropped to 0.0343m3,after lightweight size optimization,the axle housing stress and deformation,life and safety factors are little difference with before optimization,it is indicating that meet the requirements of lightweight of axle housing.